Photochemical cyclocondensation of 1-arylthio-2-azidoanthraquinones with phenols - Klimenko, L. S.; Sirazhetdinova, N. S.; Savel’ev, V. A.; Martyanov, T. P.; Korchagin, D. V. (Russian chemical bulletin, 2016)
Photolysis of 1-arylthio-2-azidoanthraquinones in DMSO in the presence of phenols leads to the formation of 5 H -naphtho[2,3- c ]phenothiazine-8,13-diones, in which the nitrogen atom is covalently bonded with the phenyl ring of the introduced phenol. As a result, poorly available polycyclic phenothiazine derivatives were obtained in one step in high yields. The cyclo-condensation with phenols was found to proceed only photochemically.